Patient perspectives on switching disease-modifying therapies in the NARCOMS registry - Salter AR; Marrie RA; Agashivala N; Belletti DA; Kim E; Cutter GR; Cofield SS; Tyry T (Patient Preference and Adherence, 2014)
Amber R Salter,1 Ruth Ann Marrie,2,3 Neetu Agashivala,4 Daniel A Belletti,4 Edward Kim,4 Gary R Cutter,1 Stacey S Cofield,1 Tuula Tyry51Department of Biostatistics, University of Alabama at Birmingham, Birmingham, AL, USA; 2Department of Internal Medicine, 3Department of Community Health Sciences, University of Manitoba, Winnipeg, MB, Canada; 4Novartis Pharmaceutical Corporation, East Hanover, NJ, USA; 5Division of Neurology, St. Joseph’s Hospital and Medical Center, Phoenix, AZ, USAIntroduction: The evolving landscape of disease-modifying therapies (DMTs) for multiple sclerosis raises important questions about why patients change DMTs. Physicians and patients could benefit from a better understanding of the reasons for switching therapy. Purpose: To investigate the reasons patients switch DMTs and identify characteristics associated with the decision to switch.Method: The North American Research Committee on Multiple Sclerosis (NARCOMS) Registry conducted a supplemental survey among registry participants responding to the 2011 update survey. The supplemental survey investigated reasons for switching DMT, origin of the discussion of DMT change, and which factors influenced the decision. Chi-square tests, Fisher’s exact tests, and logistic regression were used for the analyses. Results: Of the 691 eligible candidates, 308 responded and met the inclusion criteria (relapsing disease course, switched DMT after September 2010). The responders were 83.4% female, on average 52 years old, with a median (interquartile range) Patient-Determined Disease Steps score of 4 (2–5). The most recent prior therapy included first-line injectables (74.5%), infusions (18.1%), an oral DMT (3.4%), and other DMTs (4.0%). The discussion to switch DMT was initiated almost equally by physicians and participants. The primary reason for choosing the new DMT was based most frequently on physician’s recommendation (24.5%) and patient perception of efficacy (13.7%). Conclusion: Participants frequently initiated the discussion regarding changing DMT, although physician recommendations regarding the specific therapy were still weighed highly. Long-term follow-up of these participants will provide valuable information on their disease trajectory, satisfaction with, and effectiveness of their new medication. Keywords: multiple sclerosis, health communication